Place, Sport and Globalization: Making sense of the marca Barça - Shobe, Hunter (Treballs de la Societat Catalana de Geografia, 2008)
The case of Football Club (FC) Barcelona provides a compelling case for examining the impact of globalization on the place/identity role of football clubs. FC Barcelona has deep historical connections to Barcelona and Catalonia. These connections were de-emphasized by the clubs leadership under Josep Lluís Núñez (1978-2000) and Joan Gaspart (2000-2003) and promoted again by Joan Laporta and his directors (elected in 2003). At the same time, under Laporta, FC Barcelona has developed into a successful global brand. How are we to understand this renewed focus on the local and national discourses of place while the team is simultaneously promoted as a global brand? Although the local and global discourses seem to be at odds, the club leadership seamlessly promotes la marca Barça (the Barça Brand) while repoliticizing the club with an explicitly catalanista discourse. The global and local discourses are not mutually exclusive. Rather, the local is drawn upon in constructing the global discourse and the global is implicated in the reproduction of the local (Massey, 1994, p.120).